Strengthening the Electromigration Resistance of Nanoscaled Copper Lines by (3-aminopropyl)trimethoxysilane Self-Assembled Monolayer. (24th August 2021) - Fang, Jau-Shiung; Lee, Ching-En; Cheng, Yi-Lung; Chen, Giin-Shan
Abstract : A nanoscaled copper (Cu) line is subject to aggravated electromigration after prolonged use, and thus the use of ultrathin barrier/capping layer without degrading its electrical properties is increasingly needed. The aim of this study is to investigate the electromigration resistance of Cu interconnect strengthened by a self-assembled monolayer of (3-aminopropyl)trimethoxysilane (APTMS-SAM) and to develop an entirely wet chemically process for the fabrication of Cu lines. The Cu line with its bottom and sidewalls coated by an APTMS-SAM remains intact and yields the lowest resistivity of 1.80 μ Ω-cm even after 500 °C annealing. The resistance of the Cu line against electromigration is remarkedly strengthened by using the APTMS-SAM as a molecular thick barrier due to a low relative diffusion rate of atoms under a constant current stressing, leading to an enhancement of thermal stability by at least 100 °C. The depletion of Cu atoms of a bare Cu line is observed to start from its top area, suggesting surface diffusion is the dominating electromigration mechanism. The enhancement of the Cu interconnect encapsulated by an APTMS-SAM is thus proposed, which indeed serves as a barrier to strengthen the electromigration resistance and enhance the thermal stability of the nanoscaled Cu line.